Microstructure and properties of hypoeutectic silumin treated by high-current pulsed electron beams - Ivanov, Yu.F.; Zagulyaev, D.V.; Nevskii, S.A.; Gromov, V.Е.; Sarychev, V.D.; Semin, A.P. (Успехи физики металлов, 2019)
The structural-phase states, microhardness, and tribological properties of hypoeutectic silumin after electron-beam treatment are studied by the methods of contemporary physical materials science. The object of the study is hypoeutectic АК10М2Н-type silumin containing 87.88 wt.% of Al and 11.1 wt.% of Si as the base components. Методами сучасного фізичного матеріалознавства досліджено структурно-фазові стани, мікротвердість і трибологічні властивості доевтектичного силуміну після електронно-пучкового оброблення. Об єктом дослідження був доевтектичний силумін марки АК10М2Н із вмістом 87,88 ваг.% Al й 11,1 ваг.% Si як головних компонентів. Методами современного физического материаловедения исследованы структурнофазовые состояния, микротв рдость и трибологические свойства доэвтектического силумина после электронно-пучковой обработки. Объектом исследования являлся доэвтектический силумин марки АК10М2Н с содержанием 87,88 вес.% Al и 11,1 вес.% Si как главных компонентов.